REDUPLICATION OF VERB IN MUNA LANGUAGE - ADERLAEPE . (Gema Pendidikan, 2019)
This research aims at describing the types and functions of verb reduplication in Muna language. Problems of the research are: (1) what types of verb reduplication in Muna language? (2) what are the functions of reduplication found on verb in Muna language? Data of the research were taken by using the techniques of noting, translation, introspection, and elicitation. The achieved data  were analyzed by following the steps: (1) made the classification, (2) determine the basic element (stem) of every reduplication, (3) pay attention to the process of reduplication, (4) and determine the function of reduplication occur on verbs.  Results of the research are as follows:There are three types of verb reduplication in Muna language, namely: full,  partial, and affixed reduplications.  Partial reduplication of verb in Muna language consists of regressive and progressive reduplications.  In affixed reduplicaton, the kinds of affixes role in the reduplication process are: suffix –I which presents in the forms of suffix –pi, -ni, -li, and –mi;  prefix  sa-;  and confix  po-li.               Full reduplication on verb in Muna language functions to state repeatitive activity and relax condition or activity done to relax.  On the other hand, partial reduplication in the form of regressive reduplication functions to state repeatitive and serious activities, whereas the progressive one states reciprocal activity done by people in group.  The last one, affixed reduplication that attached by suffix  -pi, -li, and –mi states repeatitive and suffix –ni states an activity done seriously.  Reduplication with prefix sa- states frequentive activity and the reduplication attached by confix po-li that states reciprocality and repeatitive activity.   Key Words: Reduplication, Verb, Affix, Morphological Process, And Muna Language